Aplikasi Jarak Grow Light dan Fitohormon Alami Untuk Meningkatkan Produksi dan Kandungan Klorofil Microgreen Kacang Tunggak (Vigna Unguiculata L) - Komang Tri Astiti Sari; Anung Wahyudi; Ni Siluh Putu Nuryanti (Jurnal Penelitian Pertanian Terapan, 2025)
Urban farming by cultivating microgreens is an alternative for fulfilling food security. Microgreen is a technique for cultivating vegetables in urban areas, with a harvest time of 7-14 days after sowing. Increased cowpea microgreen production is influenced by growing light and natural phytohormones. This research aimed to determine the role of grow light distance and natural phytohormones in increasing production and chlorophyll content in cowpea microgreens. This research used a Randomized Block Design (split-plot) consisting of 2 factors. The 1st factor, A1= 20 cm, A2= 40 cm and A3= 60 while the 2nd factor, B0 = Aquades, B1 = 50% Aquades + 50% Coconut Water, B2= 50% Aquades + 50% Onion Extract , B3 = Aquades 50% + Coconut Water 25% + Onion Extract 25%. The research results showed that the treatment of 50% distilled water + 25% coconut water + 25% shallot extract at a grow light distance of 60 cm produced the highest value for the plant height parameter, namely 16.70 cm. The highest chlorophyll content was in the combination of 50% distilled water + 50% coconut water at a distance of 20 cm, namely 52.97 mg/g. The 60 cm grow light distance treatment produced the highest plant height, namely 18.88 cm, the heaviest wet weight parameter using a 40 cm grow light distance, namely 1.43 grams and a 20 cm grow light distance produced a high chlorophyll content, namely 38.40 mg/g. The aquadest treatment produced the highest plant height, namely 14.33 cm, while the optimal number of leaves and fresh weight used the 50% aquades + 25% coconut water + 25% shallot extract treatment, namely 5 pieces and 1.38 g and the 50% aquades + coconut water treatment. 50% produces a high chlorophyll content of 24.87 mg/g.